Efecto de la combinación de las concentraciones del 6- Bencilaminopurina y del medio Murashige y Skoog, 1962 en el establecimiento in vitro de Prosopis pallida, Trujillo, 2018. - CAMPOS LEÓN, Diego José (2019)
In Peru, Prosopis pallida, is the main symbol of the dry forests of the north with great economic importance for the region, for the multiple uses as raw material. The methods of sexual propagation by seeds and asexual propagation by cuttings are inefficient. Therefore, we set out to investigate the effect of the combination of the concentrations of 6- Bencilaminopurine and the basal medium of Murashige and Skoog, 1962 on in vitro seed establishment. The experimental unit was the scarified seed by the mechanical method, the treatments were t1 (1 MS and 0.00 ppm of BAP), t2 (1 MS and 0.25 ppm of BAP), t3 (1 MS and 0.50 ppm of BAP), t4 (1/2 MS and 0.00 ppm of BAP), t5 (1/2 MS and 0.25 ppm of BAP), t6 (1/2 MS and 0.50 ppm of BAP), t7 (1/3 MS and 0.00 ppm of BAP), t8 (1/3 MS and 0.25 ppm of BAP), t9 (1/3 MS and 0.50 ppm of BAP), the research work was carried out in the laboratory of the institute of potato and Andean crops -UNT, during five months. A design of complete blocks was applied at random, with three repetitions, nine treatments and eight sample units. The data were analyzed by ANOVA and Tukey tests. It is concluded that the 1/2 Murashige and Skoog medium with 0.00 ppm BAP is best for seedling length (T4) and the 1/3 Murashige and Skoog medium with 0.00 ppm BAP is best for the number of roots of Prosopis pallida H.B.K (T7) seedlings.